Hubungan Pengetahuan dan Sikap dengan Perilaku Pencegahan Penularan TB pada Penderita TB Paru Dewasa di Puskesmas Pakis Aji - Afrilya Adhiba Antonilla (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: Tuberculosis (TB) is the biggest cause of death after cardiovascular disease and respiratory tract disease, the number one type of infectious disease which is still a problem in Indonesia and the world. Jepara Regency is currently recorded as a district with TB case findings reaching 107.96. And the development of Tuberculosis cases at the Pakis Aji Community Health Center, Jepara Regency in 2021 was 36 sufferers. The aim of this research is to determine the relationship between knowledge and attitudes and behavior to prevent transmission of Tuberculosis disease in adult Tuberculosis sufferers in the Pakis Aji Community Health Center working area, Jepara Regency. Method: This research is an analytical observational study with a cross sectional approach. In this research, observations or measurements of variables are carried out at a time determined by the researcher. This research uses the Quota Sampling technique. Data collection was carried out by direct interviews guided by a questionnaire. Results: The results of the study show that there is no relationship between respondents' knowledge and behavior in preventing Tuberculosis transmission in the Pakis Aji Community Health Center working area, Jepara Regency with a p value of 0.531 > 0.05. Meanwhile, the relationship between attitudes and behavior to prevent Tuberculosis transmission shows that there is a relationship with a p value of 0.013 < 0.05. Conclusion: the behavior of preventing tuberculosis transmission in the Pakis Aji Community Health Center working area, Jepara Regency is still not optimal, which is influenced by several factors from the sufferer or family. Advice that can be given to sufferers and their families is to implement recommendations for preventing Tuberculosis transmission from health agencies, providing support and motivation to TB sufferers so they can break the chain of transmission of Tuberculosis.